Social Media in an Emergency: Use of Social Media in Rescuing Abducted School Girls in Nigeria - Maigari, Muhammad Abdullahi; Abdul-Qadir, Uthman Abdullahi (Dhaulagiri Journal of Sociology and Anthropology, 2019)
This paper examines the abduction of the schoolgirls in Chibok Local Government Area of Borno State, Nigeria in 2014. The paper examined how the abduction of the schoolgirls generated responses and support for the rescue of the abducted girls from people and organization from different parts of the globe. The Islamists terrorist organization operating in Borno State has attracted the attention of the world since 2009 when they started attacking government establishments and security installations northeast which later escalated to major cities in Northern Nigeria. Methodologically, the paper utilized secondary sources of data to analyze the phenomenon studied. The paper revealed that the development and innovations in information and communication technology which dismantled traditional and colonial boundaries enabled people to express support, solidarity and assist victims of conflict who resides millions of Kilometers away. This shows that Internet-based communications technology has reduced the distance of time and space that characterised traditional mass media. The campaign for the release of the schoolgirls on the social media platforms particularly Twitter and Facebook has tremendously contributed to the release of some of them. Furthermore, the girls freed from abduction have received proper attention: education and reintegration programmes which enable them to start post-abduction life. In this regard, social media has become a tool for supporting the government in moments of security challenges which the Bring Back Our Girls campaign attracted foreign and domestic assistance to Nigeria in the search of the abducted girls and the fight against the Islamist insurgents.